Dental Health Knowledge Improvement about Malocclusion After Oral and Dental Health Empowerment at Miftahul Ulum Melirang Islamic Junior High School, Melirang Village, Bungah District, Gresik - Ardani, I Gusti Aju Wahju; Narmada, Ida Bagus; Rahmawati, Dwi (Faculty of Dental Medicine Universitas Airlangga, 2022)
Background: Malocclusion is one of dental health problem that may affect the oral health in adolescences. The dental health education delivered is expected to be able to change the dental health behaviour of individuals or communities from unhealthy to healthy behaviour. Purpose: To increase knowledge of oral health, especially the level of knowledge of malocclusion by means of empowerment of dental health knowledge at Madrasah Tsanawiyah Miftahul Ulum Melirang Junior High School, Gresik. Methods: A total of 100 junior high school children from grade tenth, eleventh, twelfth were included in the study. Data was collected by instructing participants to fill out a pre-test questionnaire on Google drive, then a teledentistry was conducted and ended by filling out a post-test questionnaire to determine the increase in oral health knowledge for evaluation of dental health empowerment. Results: The main level of knowledge of dental and oral health is good (50%), moderate (40%) and low (10%). Knowledge about dental malocclusion is only 40% who have good knowledge about malocclusion, others are low enough to reach 20% knowledge and other respondents have moderate 40%. After the dental health empowerment program, the knowledge of the participant regarding the oral health was enhanced. Conclusion: the dental and oral health empowerment was performed successfully that increased the level of knowledge of children and teachers is still less than optimal about knowledge of malocclusion, so it is necessary to carry out socialization actions regarding the impact of malocclusion.